Penerapan Metode Demonstrasi untuk Meningkatkan Keterampilan Berbicara Bahasa Indonesia Siswa Kelas V.B SD Negeri 7 Cakranegara - Mozarita, Baiq Megarani (YASIN, 2022)
The objectives to be achieved through this research activity are: To find out that the demonstration method can improve speaking skills in learning Indonesian for class V.B students at SD Negeri 7 Cakranegara for the 2021/2022 academic year. The subjects of this study were 25 class VI.A students at SD Negeri 7 Cakranegara, consisting of 14 female students and 11 male students. The stages of this research include: (1) planning, (2) implementing actions, (3) observing, and (4) reflecting in each cycle. The result of the research is that the demonstration method can improve the speaking skills of class V.B students at SD Negeri 7 Cakranegara. This is supported by the increase in the average learning outcomes from pre-action by 56.00% to 76.00% in cycle I, increasing to 100 in cycle II at the end of learning to speak. The achievement of the average score in cycle II shows that students have met the minimum completeness criteria of 75. Research to improve students' speaking skills using the demonstration method has yielded results in the form of changes in students who were initially hesitant when practicing to be more daring in practice. The mistakes made by students have also decreased. Students also become more active in learning to speak. The activeness of students in learning activities is marked by an increase in student activity in asking, giving opinions and responding to the example of the presenter as well as increasing student confidence when advancing to practice in front of the class. Students have been able to practice speaking well and meet the criteria as skilled at speaking.